Managers skills in organizations of the palmicultor sector in department of Cesar – Colombia - García Payares, Francisco José (2017)
Fil: García Payares, Francisco José. Universidad Popular del Cesar. Facultad de Ciencias Administrativas, Contables y Económicas; Colombia.